Némirovsky lit Maurois : un texte en langue russe méconnu des Français - Marco Caratozzolo (Revue Italienne d'Etudes Françaises, 2023)
In 1931, Irène Némirovsky published a review of André Maurois's biography of Turgenev in a Russian émigré literary magazine called Čisla. This review seems important to us precisely because it was written in Russian. We offer the text of this review in the French translation, with an introduction and a commentary.